Data and metadata: Concepts and relationships - Arakaki, Ana Carolina Simionato [UNESP]; Arakaki, Felipe Augusto [UNESP] (My University, 2020)
The interdisciplinarity of research in related areas can present many contributions to the development of theories. However, it can also provide terminological confusion. Thus, the importance of discussing these concepts and avoiding nomenclature misconceptions is highlighted. For this reason, the objective of this work is to discuss and relate data and metadata concepts in Information Science. The research is characterized by an exploratory analysis methodology, making it possible to identify conceptual elements from the scientific literature, analyzing the information from Perspectivism. As a result, the definitions and relationships between ‘data’ and ‘metadata’ identified in the literature review are presented. It is considered that the survey and the discussions presented in the text demonstrate several relationships between the concepts, mainly linked to the Semantic Web, Data Science, Big data, among others, raising the need for further definitions and reflections in the area of Science of the Information, due to divergences in conceptual perspectives.
Datos y metadatos: Conceptos y relaciones
Dados e metadados: Conceitos e relações
Keywords: Data; Data and metadata; Information Science; Metadata